Endurance capacity impairment in cold air ranging from skin cooling to mild hypothermia - Wallace, P. J.; Hartley, G. L.; Nowlan, J. G.; Ljubanovich, J.; Sieh, N.; Taber, M. J.; Gagnon, D. D.; Cheung, S. S. (Journal of Applied Physiology, 2024)
We tested the effects of cold air (0°C) exposure on endurance capacity to different levels of cold strain ranging from skin cooling to core cooling of delta-1.0°C. Ten males completed a randomized, crossover, control study consisting of a cycling time to exhaustion (TTE) at 70% of their peak power output following: 1) 30-min of exposure to 22°C thermoneutral air (TN), 2) 30-min exposure to 0°C air leading to a cold shell (CS), 3) 0°C air exposure causing mild hypothermia of -0.5°C from baseline rectal temperature (HYPO-0.5°C), and 4) 0°C air exposure causing mild hypothermia of -1.0°C from baseline rectal temperature (HYPO-1.0°C). The latter three conditions tested TTE in 0°C air. Core temperature and seven-site mean skin temperature at the start of the TTE were: TN (37.0 ± 0.2°C, 31.2 ± 0.8°C), CS (37.1 ± 0.3°C, 25.5 ± 1.4°C), HYPO-0.5°C (36.6 ± 0.4°C, 22.3 ± 2.2°C), HYPO-1.0°C (36.4 ± 0.5°C, 21.4 ± 2.7°C). There was a significant condition effect (P = 0.001) for TTE, which from TN (23.75 ± 13.75 min) to CS (16.22 ± 10.30 min, delta-30.9 ± 21.5%, P = 0.055), HYPO-0.5°C (8.50 ± 5.23 min, delta-61.4 ± 19.7%, P = 0.001), and HYPO-1.0°C (6.50 ± 5.60 min, delta-71.6 ± 16.4%, P = 0.001). Furthermore, participants had a greater endurance capacity in CS compared with HYPO-0.5°C (P = 0.046), and HYPO-1.0°C (P = 0.007), with no differences between HYPO-0.5°C and HYPO-1.0°C (P = 1.00). Endurance capacity impairment at 70% peak power output occurs early in cold exposure with skin cooling, with significantly larger impairments with mild hypothermia up to delta-1.0°C.